The role of modern medicine in clarifying definitions in Islamic jurisprudence (Ta’rifaats fi al-Fiqh) - Shahar, Mohammad Arif (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
In the usual circumstances, the medical professional is consulted by Islamic scholars when a problem related to medicine involving Muslim society arises; where a specific fatwa (Islamic ruling) is needed. Commonly, in this situation, there are possible implications on halaal (permissibility) and haraam (prohibitions) related to the medical conditions or issues. The contribution of modern medicine in understanding Islamic Law is more than situational. Modern medicine is seen to influence classical rulings in Islamic law related to everyday life. Advances in medicine may help to clarify, sometimes redefine classical concepts and terminologies in Islamic Jurisprudence (ta’rifaats fi al-fiqh). This subsequently changes the interpretations of rulings in Islamic Law. These rulings involve Muslims’ daily life, not just for specific medical conditions, illness or therapies.